2023
DOI: 10.3390/cancers15072150
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of MR-Based Radiogenomic Models to Differentiate Atypical Lipomatous Tumors from Lipomas

Abstract: Background: The aim of this study was to develop and validate radiogenomic models to predict the MDM2 gene amplification status and differentiate between ALTs and lipomas on preoperative MR images. Methods: MR images were obtained in 257 patients diagnosed with ALTs (n = 65) or lipomas (n = 192) using histology and the MDM2 gene analysis as a reference standard. The protocols included T2-, T1-, and fat-suppressed contrast-enhanced T1-weighted sequences. Additionally, 50 patients were obtained from a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…One study [ 28 ] examined the associations between temporal alterations observed in MRI, based on qualitative/semi-quantitative features and radiomics features, and the survival outcomes and histopathological characteristics. Foreman et al [ 48 ] developed radiogenomic models with the purpose of predicting the MDM2 gene amplification status and distinguishing between atypical lipomatous tumours and lipomas based on preoperative MRI scans. Nine studies assessed the role of radiomics features for evaluating the toxicity, management and treatment responses of patients with STSs treated with radiotherapy and/or chemotherapy [ 23 , 44 , 49 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [ 28 ] examined the associations between temporal alterations observed in MRI, based on qualitative/semi-quantitative features and radiomics features, and the survival outcomes and histopathological characteristics. Foreman et al [ 48 ] developed radiogenomic models with the purpose of predicting the MDM2 gene amplification status and distinguishing between atypical lipomatous tumours and lipomas based on preoperative MRI scans. Nine studies assessed the role of radiomics features for evaluating the toxicity, management and treatment responses of patients with STSs treated with radiotherapy and/or chemotherapy [ 23 , 44 , 49 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Timbergen et al [ 47 ] evaluated MRI radiomics models for distinguishing between desmoid-type fibromatosis and STSs. As previously mentioned, Foreman et al [ 48 ] attempted to develop radiogenomic models with the goal of distinguishing between atypical lipomatous tumours and lipomas by analysing the MDM2 gene amplification status using preoperative MRI scans. Aouadi et al [ 60 ] examined several datasets, in particular the LIPO dataset [ 61 ] for distinguishing between well-differentiated liposarcoma and lipoma, and the Desmoid dataset [ 61 ] for differentiating desmoid-type fibromatosis from extremity STSs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study serves as a proof of concept, laying the groundwork for further developments. Other studies have investigated the role of radiomics both in discriminating between benign and malignant soft-tissue tumors [41,42] and in distinguishing between lipoma and liposarcoma/ atypical lipomatous tumors [43,44]. Additionally, other studies have explored the potential of radiomics for identifying high-grade STS [45].…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 99%